Open-field mouse brain PET: design optimisation and detector characterisation. (13th July 2017) - Kyme, Andre Z; Judenhofer, Martin S; Gong, Kuang; Bec, Julien; Selfridge, Aaron; Du, Junwei; Qi, Jinyi; Cherry, Simon R; Meikle, Steven R
Abstract: 'Open-field' PET, in which an animal is free to move within an enclosed space during imaging, is a very promising advance for neuroscientific research. It provides a key advantage over conventional imaging under anesthesia by enabling functional changes in the brain to be correlated with an animal's behavioural response to environmental or pharmacologic stimuli. Previously we have demonstrated the feasibility of open-field imaging of rats using motion compensation techniques applied to a commercially available PET scanner. However, this approach of 'retro-fitting' motion compensation techniques to an existing system is limited by the inherent geometric and performance constraints of the system. The goal of this project is to develop a purpose-built PET scanner with geometry, motion tracking and imaging performance tailored and optimised for open-field imaging of the mouse brain. The design concept is a rail-based sliding tomograph which moves according to the animal's motion. Our specific aim in this work was to evaluate candidate scanner designs and characterise the performance of a depth-of-interaction detector module for the open-field system. We performed Monte Carlo simulations to estimate and compare the sensitivity and spatial resolution performance of four scanner geometries: a ring, parallel plate, and two box variants. Each system was based on a detector block consisting of a 23 × 23 array of 0.785 × 0.785 × 20 mm 3 LSO crystals (overall dim. 19.6 × 19.6 × 20 mm). We found that a DoI resolution capability of 3 mm was necessary to achieve approximately uniform sub-millimetre spatial resolution throughout the FoV for all scanners except the parallel-plate geometry. With this DoI performance, the sensitivity advantage afforded by the box geometry with overlapping panels (16% peak absolute sensitivity, a 36% improvement over the ring design) suggests this unconventional design is best suited for imaging the mouse brain. We also built and characterised the block detector modelled in the simulations, including a dual-ended readout based on 6 × 6 arrays of through-silicon-via silicon photomultipliers (active area 84%) for DoI estimation. Identification of individual crystals in the flood map was excellent, energy resolution varied from 12.4% ± 0.6% near the centre to 24.4% ± 3.4% at the ends of the crystal, and the average DoI resolution was 2.8 mm ± 0.35 mm near the central depth (10 mm) and 3.5 mm ± 1.0 mm near the ends. Timing resolution was 1.4 ± 0.14 ns. Therefore, the DoI detector module meets the target specifications for the application and will be used as the basis for a prototype open-field mouse PET scanner.